SOLUBILITY ENHANCEMENT OF CELECOXIB BY SOLID DISPERSION TECHNIQUE AND INCORPORATION INTO TOPICAL GEL - SHAIKH, AMRIN; BHIDE, PRASHANT; NACHINOLKAR, REESHWA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the present investigation was to design gels for the topical delivery of celecoxib and evaluate with an aim to increase its penetration through the skin and thereby its flux. Method: The solubility of celecoxib is shown to be increased by preparing solid dispersions (SDs) using carriers such as mannitol, polyvinylpyrrolidone (PVP-K30), polyethylene glycol (PEG) 6000 and urea by solvent evaporation, fusion, and coevaporation methods. In vitro release profile of all SD was comparatively evaluated and studied against the pure drug. The prepared SD was subjected for percent practical yield, drug content, infrared spectroscopy, differential scanning calorimetry analysis, X-ray diffraction studies, and scanning electron microscopy (SEM) imaging. The celecoxib gel was prepared using hydroxypropyl methyl cellulose (HPMC) and Carbopol containing a permeation enhancer dimethyl sulfoxide (DMSO) at different proportions and evaluated for drug content, pH, viscosity, spreadability, extrudability, stability, and in vitro drug release. Results: Faster dissolution rate was exhibited by SD containing 1:5 ratio of celecoxib: PVP K-30 prepared by coevaporation method. In vitro drug release of celecoxib, gels revealed that formulation with HPMC has higher drug release as compared to Carbopol. Conclusion: The increase in dissolution rate for SD is observed in the following order of PVP K-30>urea>mannitol>PEG 6000. The CPD5 gel containing a SD CP5 and 20% DMSO showed the best in vitro release 74.13% at the end of 6 h.